2011
DOI: 10.4103/0970-2113.80321
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic evaluation of heart in chronic obstructive pulmonary disease patient and its co-relation with the severity of disease

Abstract: Background:Chronic obstructive pulmonary disease (COPD) has considerable effects on cardiac functions, including those of the right ventricle, left ventricle, and pulmonary blood vessels. Most of the increased mortality associated with COPD is due to cardiac involvement. Echocardiography provides a rapid, noninvasive, portable, and accurate method to evaluate the cardiac changes.Aims:To assess the cardiac changes secondary to COPD by echocardiography and to find out the correlation between echocardiographic fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
27
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(32 citation statements)
references
References 26 publications
4
27
0
1
Order By: Relevance
“…(21,22). In addition, a recent study showed evidence of diastolic dysfunction in 47.5% (24) of COPD patients. However, Freixa et al found a lower frequency of this echocardiographic alteration (12%) in COPD patients in their first hospital admission (25).…”
Section: Discussionmentioning
confidence: 98%
“…(21,22). In addition, a recent study showed evidence of diastolic dysfunction in 47.5% (24) of COPD patients. However, Freixa et al found a lower frequency of this echocardiographic alteration (12%) in COPD patients in their first hospital admission (25).…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, the difference in the frequency of LVDD in patients with COPD between the present and previous studies might be due to different distribution of COPD stages, age, sex, and comorbidities. In addition, a recent study 12 showed diastolic dysfunction in 47.5% of patients with COPD, and only 27.5% of their patients had severe/very severe COPD.…”
Section: Discussionmentioning
confidence: 98%
“…1-4 Functional decline is often associated with concomitant pulmonary hypertension (PH) and right ventricular (RV) dysfunction 2, 5-10 . Cardiac magnetic resonance imaging (cMRI) is the gold standard for the assessment of both the morphological and functional characteristics of the RV particularly in patients with COPD in whom echocardiographic assessment is often not possible 11-14 .…”
mentioning
confidence: 99%